Expert system on efficiency evaluation of continuous flow grain dryer - Walczak, Renata (Studia Informatica. System and information technology, 2022)
The purpose of the paper is to present a concept of energy efficiency and financial evaluation of counterflow dryer. Energy efficiency and many other efficiency indexes of the dryer and all additional devices like heater, heat exchangers, tubing and fans are calculated. Expert system provides also the financial evaluation of the investment. Many investments could be considered. The system provides the user with suggestions about the best dryer for him/her. Expert system also enables evaluation of energy saving improvements. The energy savings for dryer installation sections are calculated. Cost savings are compared with investment value. The best energy saving project could be selected on the base of selection algorithm. Expert system could be used for existing and new-designed dryers.